Pediatric blunt renal trauma practice management guidelines: Collaboration between the Eastern Association for the Surgery of Trauma and the Pediatric Trauma Society. Issue 5 (May 2019) - Hagedorn, Judith C.; Fox, Nicole; Ellison, Jonathan S.; Russell, Robert; Witt, Cordelie E.; Zeller, Kristen; Ferrada, Paula; Draus, John M.
Abstract : BACKGROUND: Injury to the kidney from either blunt or penetrating trauma is the most common urinary tract injury. Children are at higher risk of renal injury from blunt trauma than adults, but no pediatric renal trauma guidelines have been established. The authors reviewed the literature to guide clinicians in the appropriate methods of management of pediatric renal trauma. METHODS: Grading of Recommendations Assessment, Development and Evaluation methodology was used to aid with the development of these evidence-based practice management guidelines. A systematic review of the literature including citations published between 1990 and 2016 was performed. Fifty-one articles were used to inform the statements presented in the guidelines. When possible, a meta-analysis with forest plots was created, and the evidence was graded. RESULTS: When comparing nonoperative management versus operative management in hemodynamically stable pediatric patient with blunt renal trauma, evidence suggests that there is a reduced rate of renal loss and blood transfusion in patients managed nonoperatively. We found that in pediatric patients with high-grade American Association for the Surgery of Trauma grade III-V (AAST III-V) renal injuries and ongoing bleeding or delayed bleeding, angioembolization has a decreased rate of renal loss compared with surgical intervention. We found the rate of posttraumatic renal hypertension to be 4.2%. CONCLUSION: Based on the completed meta-analyses and Grading of Recommendations Assessment, Development and Evaluation profile, we are making the following recommendations: (1) In pediatric patients with blunt renal trauma of all grades, we strongly recommend nonoperative management versus operative management in hemodynamically stable patients. (2) In hemodynamically stable pediatric patients with high-grade (AAST grade III-V) renal injuries, we strongly recommend angioembolization versus surgical intervention for ongoing or delayed bleeding. (3) In pediatric patients with renal trauma, we strongly recommend routine blood pressure checks to diagnose hypertension. This review of the literature reveals limitations and the need for additional research on diagnosis and management of pediatric renal trauma. LEVEL OF EVIDENCE: Guidelines study, level III.